Innovative Personalized Business Model in the Field of Hair Restoration: Author’s Methods as a Factor in Strengthening Women’s Entrepreneurship - Romaniuk, Maryna (Академічні візії, 2023)
The article explores the prospects for the development of women’s entrepreneurship in the beauty industry through the implementation of proprietary techniques - SensHair and Nanoker - in the hair restoration process. The purpose of the study is to substantiate the effectiveness of implementing personalized business models based on the proprietary technologies SensHair and Nanoker as a factor in strengthening women’s entrepreneurship, building an expert brand, and enabling innovative self-realization in the service economy. The study employs business modeling tools (Canvas model), financial and economic forecasting, comparative analysis, and case study methods. The research justifies two effective business models in the hair restoration sector: a small personalized salon and a large studio with franchising potential. The first model focuses on service individualization, high client trust, and flexible management, making it attractive for the early stage of women’s entrepreneurial development. The second model relies on standardized procedures scaled under a single brand, with clearly defined business processes and marketing templates, laying the groundwork for expansion through franchising. Each model reflects adaptation to the needs of a specific target audience, integration of emotional support for clients, clear service differentiation by complexity and cost, and scalability potential. The use of proprietary care techniques provides not only a competitive advantage but also high economic efficiency: the return on investment (ROI) exceeds 22–25% per month, with a payback period of approximately four months. The proposed business models based on SensHair and Nanoker demonstrate that innovative women-led enterprises can successfully combine ethics, expertise, and economic viability. These techniques are suitable both for individual business launches and for future scaling through education, salon networks, or franchising. The study highlights the potential of women’s entrepreneurship as a socially impactful and economically profitable phenomenon.